Crenicichla taikyra (Teleostei: Cichlidae), a new species of the pike cichlids from the middle Río Paraná - Casciotta, Jorge Rafael (2013)
Crenicichla taikyra, new species, is described from the middle río Paraná, Argentina. Crenicichla taikyra is distinguished from the other species of the genus by the following combination of characters: lower pharyngeal tooth plate stout, bearing molariform teeth, ascending arm of premaxilla longer than the dentigerous arm, posterior edge of preoperculum serrated, a well developed suborbital stripe, and absence of scattered dark dots on flanks. Molariform teeth on pharyngeal jaws is a derived character among Crenicichla species, however this character state has appeared several times in unrelated species.